Power Sector Reforms and Electricity Deficit in Nigeria: Stakeholders’ Perspective - Adelowo, Caleb Muyiwa; Fadare, Mary Oladuni (International Journal of Energy Economics and Policy, 2023)
Inadequate generation and distribution of electricity constitute major bottlenecks to productivity and industrial growth in Nigeria. Over the years, several reforms have been implemented in the power sector but the challenges persist, and many socio-economic activities are negatively impacted. The problems are exacerbated by inconsistent policies of the government on the management of the power sector and the inefficient capacity of the private operators. In this article, we examine the kernels of power sector reforms, the depth of the reforms’ awareness, the level of implementation, and the degree to which customers were satisfied with the electricity supply. Primary data were collected through a cross-sectional survey conducted on the management and customers of electricity distribution companies in Ibadan, Ekiti and Lagos States, using two sets of validated questionnaires. Six hundred and sixty-seven (667) management and staff members, and one thousand one hundred and nineteen (1,119) customers participated in the survey. The results show that a major reform to the sector is privatisation, leading to the unbundling of the Power Holding Company of Nigeria. Some of the measures taken to implement the reforms include staff training and redeployment, organisation restructuring, public sensitisation, disengagement of redundant staff, and introduction of more efficient monitoring and evaluation mechanisms. The study observes that a large proportion of customers are aware of the power sector reforms and understood the implications but they claimed there was no significant improvement in the power supply compared to pre-reform periods. The paper concludes with appropriate policy recommendations for the government, operators and stakeholders in the sector.